Test of polycross progenies and cultivars of alfalfa - Pozzobon, Marisa T.; Paim, Nilton R.; Schifino, Maria Teresa; Riboldi, João (Pesquisa Agropecuaria Brasileira, 2014)
Five cultivars and fifteen polycross progenies of alfalfa (Medicago sativa L.) were evaluated from May 81 to December 82 at the Estação Experimental Agronômica da UFRS, Guaíba, RS, Brazil. Total mean leaf to stem ratio (L/S) ranged from 1.48 to 1.94 (1/7 progeny and WI 318 cultivar, respectively). The L/S were higher in Autumn and highest plant mean heights in summer and spring. Total dry matter yield ranged from 6,667 to 10,950 kg.ha-1 (1/4 and 7/16 progenies, respectively), without significant differences among treatments. Mean seasonal dry matter yield distribution (kg.ha-1) ranged from 4,081 in spring, 2,186 in summer, 1,863 in winter to 1,120 in autumn. Average leaf crude protein content was 29.13%, 2.38 times higher than in stems (12.23%). A positive correlation was found between dry matter yield, initial and final number of plants/m and plant mean height, and between mean initial number of plants, percentage reduction in number and L/S. L/S showed a negative significant correlation with plants mean height. The Crioula cultivar and its progenies were more persistent and adapted to the Central Depression of Rio Grande do Sul environmental conditions.